Aplicação de um estudo de tempos e métodos em uma empresa do ramo têxtil localizada na cidade de Jardim de Piranhas-RN - Silva, Samuel Gomes da (Universidade Federal Rural do Semi-Árido, 2019)
This work has as main objective the application of a study of times and methods in a company of the textile branch located in the city of Jardim de Piranhas-RN. For that, a case study was carried out, whose main instruments of data collection were some semi-structured interviews and in loco observations. For the elaboration of the research instrument, a broad review was made in the literature and later business analysis under the perspectives of process mapping and time study, using chrono-analysis, man-machine diagram and Standard Operational Procedure (POP). The research was classified as applied, exploratory, descriptive and qualitative-quantitative. The results pointed out the standard times and the POP of each one of the analyzed activities, as well as the finding of high levels of operator idleness with the binadora machine. Thus, a study was left as a base for countless others, contributing directly to the planning and control of the production, besides propositions that aim at increase in the organizational efficiency.
Keywords: Estudo de tempos; Times study; Estudo de métodos; Methods study; Cronoanálise; Chronoanalysis; Procedimento operacional padrão; Standard operational procedure; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA